PENINGKATAN Model Interaktif untuk Internalisasi Karakter melalui Hafalan Hadits di TPQ Al-Mughni - Abdullah, Siti Fatimah; Dinamik, Titik; Sangaji , Nazmatul Lail Azis (Jurnal SOLMA, 2026)
Background: This community service program aimed to strengthen students’ Islamic character (husnul khuluq) through an interactive, short-hadith memorization model at TPQ Al-Mughni. The partner institution faced low levels of students’ understanding of hadith content and limited internalization of hadith values in daily behavior, mainly due to the lack of contextual learning practices and increasing digital exposure. Method: This program employed a descriptive, qualitative approach and was conducted over 9 structured sessions from 24 September to 22 October 2025, involving 20 students. The intervention integrated storytelling, role-play, and focused drills, supported by visual learning media. Results: Significant improvements were observed in both cognitive and affective domains. The average pre-test score of 2.15 increased to 3.65 in the post-test. The greatest improvements were found in the domains of meaning comprehension (82%) and character internalization (71%). These findings demonstrate that the interactive model effectively bridges the gap between textual memorization of hadith and the practical application of its values in students’ behavior. Conclusion: The program offers a systematic, replicable pedagogical model to strengthen character education in non-formal Islamic institutions in the digital era.